Stories of the nameless eyewitness accounts of Martial Law victims and survivors - Melencio, Gloria Esguerra (UP Los Baños Journal, 2019)
This paper features the eyewitness accounts of some 10 victims martial law in Luzon, Visayas and Mindanao. Most of the eyewitnesses belong to the lower strata of the Philippine social structure...